2016
DOI: 10.1073/pnas.1605844113
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and ubiquitin–proteasome system contribute to sperm mitophagy after mammalian fertilization

Abstract: Maternal inheritance of mitochondria and mtDNA is a universal principle in human and animal development, guided by selective ubiquitin-dependent degradation of the sperm-borne mitochon-dria after fertilization. However, it is not clear how the 26S pro-teasome, the ubiquitin-dependent protease that is only capable of degrading one protein molecule at a time, can dispose of a whole sperm mitochondrial sheath. We hypothesized that the canonical ubiquitin-like autophagy receptors [sequestosome 1 (SQSTM1), microtub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(103 citation statements)
references
References 38 publications
6
95
0
2
Order By: Relevance
“…MUL1 can also cleave sperm-derived mitochondria in a PINK1-dependent manner in zygotes [41](detailed below). Additionally, Nix/BNIP3L can induce mitophagy in a PINK1/Parkin-independent manner [42] (also shown below). Some proteins involved in Parkin-independent mitophagy pathways, such as Ambra1, Nix, and FUNDC1, also have roles in traditional Parkin-dependent mitophagy [4345].…”
Section: Overview Of Mitophagy Pathwaysmentioning
confidence: 99%
“…MUL1 can also cleave sperm-derived mitochondria in a PINK1-dependent manner in zygotes [41](detailed below). Additionally, Nix/BNIP3L can induce mitophagy in a PINK1/Parkin-independent manner [42] (also shown below). Some proteins involved in Parkin-independent mitophagy pathways, such as Ambra1, Nix, and FUNDC1, also have roles in traditional Parkin-dependent mitophagy [4345].…”
Section: Overview Of Mitophagy Pathwaysmentioning
confidence: 99%
“…In a conserved process involving concerted autophagy (mitophagy) and proteasomal degradation pathways 7 , sperm-derived mitochondria are eliminated after fertilization before the two-cell stage [8][9][10] although alternative mechanisms, including elimination of sperm mtDNA before fertilization, may operate in the mouse 11 .…”
Section: Inheritance Of Mtdna Mutationsmentioning
confidence: 99%
“…In mammalian fertilization, mitophagy naturally removes sperm-borne mitochondria via a pathway that ubiquitylates mitochondrial components for proteasomal destruction 10 . Mitophagy may be restricted to cells of the male germline, as mitochondria from mouse spermatids 1 0 6 6 VOLUME 35 NUMBER 11 NOVEMBER 2017 nature biotechnology r e v i e w but not hepatocytes are degraded 9 , which is why the process would have to be modified so that carried-over mitochondria were ubiquitylated in MRT protocols.…”
Section: Mitophagymentioning
confidence: 99%
“…Yu et al showed that the mitochondrial DNA polymerase promotes abrupt elimination of mitochondrial genomes during spermatogenesis in Drosophila [25]. Upon fertilization, proteasomal and lysosomal pathways are activated in oocytes to eliminate paternal MT and mtDNA [6,26,27]. In C. elegans, two groups have shown that paternal MTs are degraded by fertilization-induced autophagy [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, sperm-derived paternal mitochondria themselves are thought to undergo selective autophagy, which includes mitophagy. Ubiquitination of the sperm mitochondria during spermatogenesis and after-fertilization has been implicated in the targeted degradation of paternal mitochondria [27,29,31,32]. However, it is not known whether or not mtDNA degradation could be delayed in mammalian embryos because of the method of delivery of paternal mitochondrial DNA by injection .…”
Section: Discussionmentioning
confidence: 99%